Protection Indicator in the Constitutions of the European Federations - Gutorova, Alla N. (2022)
The article presents the results of a comparative legal analysis of the constitutions of European federal states (Austria, Belgium, Bosnia and Herzegovina, Germany, and Switzerland) with a view to identifying the norms that minimize human rights risks. The identification of such constitutional provisions is associated with the formalization of the protection of the human rights and freedoms, as well as its legal statuses and conditions. The research was based on a dialectical approach to the disclosure of legal phenomena and processes using general scientific (systematic and logical methods, analysis and synthesis) and specific scientific methods. The unity of the constitutional approach of the European federal states to formalize the judicial protection of the rights and freedoms of the individual (Austria, Belgium, Bosnia and Herzegovina, Germany, Switzerland) has been determined. The identification of such constitutional provisions are associated with the formalization of the protection of the human rights and freedoms, as well as its legal statuses and conditions. The Novelty of the study is carrying out the declared constitutional analysis of the defense was on the example of European federal states